Is there a sex‐shift in prevalence of allergic rhinitis and comorbid asthma from childhood to adulthood? A meta‐analysis. Issue 1 (5th December 2017) - Fröhlich, M.; Pinart, M.; Keller, T.; Reich, A.; Cabieses, B.; Hohmann, C.; Postma, D. S.; Bousquet, J.; Antó, J. M.; Keil, T.; Roll, S.
Abstract: Background: Allergic rhinitis and asthma as single entities affect more boys than girls in childhood but more females in adulthood. However, it is unclear if this prevalence sex‐shift also occurs in allergic rhinitis and concurrent asthma. Thus, our aim was to compare sex‐specific differences in the prevalence of coexisting allergic rhinitis and asthma in childhood, adolescence and adulthood. Methods: Post‐hoc analysis of systematic review with meta‐analysis concerning sex‐specific prevalence of allergic rhinitis. Using random‐effects meta‐analysis, we assessed male–female ratios for coexisting allergic rhinitis and asthma in children (0–10 years), adolescents (11–17) and adults (> 17). Electronic searches were performed using MEDLINE and EMBASE for the time period 2000–2014. We included population‐based observational studies, reporting coexisting allergic rhinitis and asthma as outcome stratified by sex. We excluded non‐original or non‐population‐based studies, studies with only male or female participants or selective patient collectives. Results: From a total of 6539 citations, 10 studies with a total of 93, 483 participants met the inclusion criteria. The male–female ratios (95% CI) for coexisting allergic rhinitis and asthma were 1.65 (1.52; 1.78) in children (N = 6 studies), 0.61 (0.51; 0.72) in adolescents (N = 2) and 1.03 (0.79; 1.35) in adults (N = 2). Male–female ratios for allergic rhinitis only were 1.25 (1.19; 1.32, N = 5) in children, 0.80 (0.71; 0.89, N = 2) in adolescents and 0.98 (0.74; 1.30, N = 2) in adults, respectively. Conclusions: The prevalence of coexisting allergic rhinitis and asthma shows a clear male predominance in childhood and seems to switch to a female predominance in adolescents. This switch was less pronounced for allergic rhinitis only.